2002
DOI: 10.1093/clinchem/48.5.699
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C: An Improved Estimator of Glomerular Filtration Rate?

Abstract: Background: Glomerular filtration rate (GFR) is routinely assessed by measuring the concentrations of endogenous serum markers such as blood urea nitrogen and serum creatinine (SCr). Although widely used, these endogenous markers are not ideal and do not perform optimally in certain clinical settings. The purpose of this review is to critically review the potential utility of cystatin C (CysC), especially in patient populations in which CysC may have an advantage over routinely used endogenous markers of GFR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 570 publications
(235 citation statements)
references
References 56 publications
7
218
1
9
Order By: Relevance
“…128,129 Studies on the sensitivity and specificity of cystatin C for detecting impaired GFR strongly suggest it to be superior diagnostic marker to creatinine for detecting impaired GFR. 130 However, caution is necessary in case of patients with malignancy or other diseases with increased activity of cyteine proteases which exhibit increased cystatin C levels irrelevant to kidney function. 131 It has been suggested that disturbance of the cystatin E/M-cathepsin pathway could contribute to dysregulated skin barrier function as observed in the inflammatory dermatoses.…”
Section: Type II Cystatins In Pathological Processesmentioning
confidence: 99%
“…128,129 Studies on the sensitivity and specificity of cystatin C for detecting impaired GFR strongly suggest it to be superior diagnostic marker to creatinine for detecting impaired GFR. 130 However, caution is necessary in case of patients with malignancy or other diseases with increased activity of cyteine proteases which exhibit increased cystatin C levels irrelevant to kidney function. 131 It has been suggested that disturbance of the cystatin E/M-cathepsin pathway could contribute to dysregulated skin barrier function as observed in the inflammatory dermatoses.…”
Section: Type II Cystatins In Pathological Processesmentioning
confidence: 99%
“…A recent review of 24 studies comparing cystatin C to serum creatinine reported that cystatin C outperformed serum creatinine in 15 studies and was at least as good in the remainder. 5 The majority of these studies examined patients with intrinsic renal disease (including pre-and post-renal transplant patients) or healthy disease-free controls. The area under the curve (AUC) constructed from receiver operator characteristic curves for all studies showed that cystatin C was a better marker of renal function than serum creatinine when compared against clearance of exogenous substances (AUC 0.95 cystatin C vs. 0.91 serum creatinine).…”
Section: Cystatin Cmentioning
confidence: 99%
“…8 -11 Therefore, cystatin C is deemed a useful biomarker of renal function. 9,12,13 Recent reports have indicated that cystatin C might also be a prognostic indicator of cardiovascular (CV) mortality. Lassus et al 14…”
Section: Introductionmentioning
confidence: 99%